Perforation of the small intestine in a non reducible spigelian hernia, by a foreign body. - Karavokyros, Ioannis; Delikonstantinou, Iraklis; Pikoulis, Evangelos (Cas Lek Cesk, 2014)
An 87 yr man was referred for abdominal pain over a pre-existing hernia in the right iliac fossa. Physical examination revealed a red painful palpable mass in the right lower abdominal quadrant. Abdominal CT scan revealed a loop of small intestine trapped into the abdominal wall. The patient underwent emergency laparotomy and the intraoperative findings consisted of a spigelian hernia, with perforation of the contained small intestine by a chicken bone (clavicle). The intestinal perforation was sutured and a polypropylene mesh plug and patch repair of the hernia was executed. The patient had an uneventful recovery and was discharged in stable condition. Our patient had a rare type of hernia with a rare complication. The arrow-shaped chicken bone led to irreducibility of the hernia and eventually to intestinal perforation. The diagnosis of spigelian hernias by history and physical examination is notoriously difficult. Recently, imaging modalities have increased preoperative diagnostic yield.
Keywords: Aged, 80 and over; Foreign Bodies; Hernia, Ventral; Herniorrhaphy; Humans; Intestinal Perforation; Intestine, Small; Male; Tomography, X-Ray Computed